Burnout syndrome in school principal. An exploratory study from a one-dimensional approach - Barraza Macías, Arturo (Avances en Supervisión Educativa, 2010)
This research aims to: a) Specify the descriptive profile Burnout Syndrome who have primary school principal, b) Establish the extent to which demographic variables influence the level of burnout syndrome reported by primary school principal, and c) determine the relationship between the level of job satisfaction and burnout syndrome reported by primary school principal. The theoretical construction of the research object was based on the approach conceptual one-dimensional and the interactive model explanatory. To achieve the stated objectives, was performed a study exploratory, correlational, cross and not experimental. For the collection of information was applied Shirom Melamed Burnout Measure of a population of 24 directors of elementary education in the of seven and eight school zones located in the city of Surango. The main results are: 1 .- that primary school managers surveyed present a mild level of burnout, 2 .- that the sociodemographic variables studied did not influence the level and 3 .- the variable job satisfaction have a significant negative correlation with level of burnout syndrome.